Allardia stoliczkae C.B. Clarke (Asteraceae) – A new record for the Uttarakhand, India - Sekar, K. Chandra; Pandey, Aseesh; Bhatt, Deepika; Dey, Dipti; bisht, Kapil; Rawal, R. S. (Indian Forester, 2018)
No Abstract.